STRENGTHENING OF CHARACTER WITH STUDENTS IN THE FAMILY ENGAGEMENT EDUCATION MUHAMMADIYAH - Fitri Puji Rahmawati (Universitas Ahmad Dahlan, 2015)
This study aimed to describe the implementation of character education that is applied in the Basic Education Muhammadiyah Surakarta through informal approach. Developed a character education in elementary involve informal education conducted at home. The main method developed in this study is descriptive-qualitative-reflective. The technique of collecting data through observation and in-depth interviews were actively involved with the teachers, parents/ guardians, and elementary school students. Data were analyzed with snowball technic of analysis models Milles Huberman. Character education involving families in the educational environment of Muhammadiyah implemented with the collaboration of school and family. Some of the programs implemented by schools include: parenting day, outbound together, study, home visit, parents and guardians of students meeting. In these activities, parents, students, and teachers get a refresher on the importance of strengthening the character and variety of information about character education.